Primary Epidermoid Cyst of the Clitoris in Adult Female Population: Three Case Reports and Introducing a Safe Surgical Approach - Mahmoudnejad, Nastaran; Mohammadi Torbati, Peyman; Zadmehr, Alireza (Urology Journal, 2020)
Epidermoid cyst (EPC) of the clitoris is a very rare cause of non-hormonal acquired clitoromegaly. Clitoral EPCs are extremely uncommon without prior history of genital surgery, trauma, circumcision, or piercing. Surgical removal with special care to avoid compromising neurovascular bundle of the clitoris is the preferred treatment. To our best knowledge, only three cases of adult female clitoral EPC without history of genital surgery, female circumcision, or medications including oral or implantable contraceptives have been reported. Herein, we describe three cases of primary EPC of the clitoris, their management, unique histopathology report, safe surgical approach, and their follow up course.